2017
DOI: 10.4314/tjpr.v16i1.24
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of <i>Dipsacus asper</i> Wallich ex Candolle (Dipsacaceae) essential oil and its activity against mosquito larvae of <i>Aedes aegypti</i> and <i>Culex pipiens</i> pallens

Abstract: Purpose: To evaluate the larvicidal activity of the essential oil of Dipsacus asper Wallich ex Candolle (Dipsacaceae) roots against the larvae of Aedes aegypti L. and Culex pipiens pallens Coquillett. Methods: Essential oil was extracted from D. asper roots by hydrodistillation and analyzed for its composition by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In the essential oil from the biotic-stressed, herbivore-damaged leaf, the presence of only two compounds has been identified that had not been found in the essential oil samples from undamaged or mechanically-damaged leaves: β-Gurjunene (2.1%) and spirolepechinene (2.5%), associated with the inducible defense of I. alba in response to damage by the grasshopper E. trilineata. Essential oil extracted from the Dipsacus asper roots exhibited larvicidal activity against Aedes aegypti and Culex pipiens; β-Gurjunene has been identified as one of the major compounds in the oil [24] . The spirolepechinene is a spirosesquiterpene found in Lepechinia bullata and of a unique structure [25] .…”
Section: Resultsmentioning
confidence: 99%
“…In the essential oil from the biotic-stressed, herbivore-damaged leaf, the presence of only two compounds has been identified that had not been found in the essential oil samples from undamaged or mechanically-damaged leaves: β-Gurjunene (2.1%) and spirolepechinene (2.5%), associated with the inducible defense of I. alba in response to damage by the grasshopper E. trilineata. Essential oil extracted from the Dipsacus asper roots exhibited larvicidal activity against Aedes aegypti and Culex pipiens; β-Gurjunene has been identified as one of the major compounds in the oil [24] . The spirolepechinene is a spirosesquiterpene found in Lepechinia bullata and of a unique structure [25] .…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the different growth environments, the accumulated active components and the quality of D. asperoides have shown marked differences in different cultivation bases [2][3][4]. At present, research on D. asperoides has primarily focused on chemical composition [5], cultivation [6], pharmacology [7], and transcriptomics [1]. Triterpenoid saponins, such as dipsacus saponin VI, macranthoidin A and HN saponin F, are the principal active ingredients of D. asperoides [8].…”
Section: Introductionmentioning
confidence: 99%